A Multifunctional Solution for Wicked Problems: Value-Chain Wide Facilitation of Legumes Cultivated at Bioregional Scales Is Necessary to Address the Climate-Biodiversity-Nutrition Nexus - Iannetta, Pietro P. M.; Hawes, Cathy; Begg, Graham S.; Maaß, Henrik; Ntatsi, Georgia; Savvas, Dimitrios; Vasconcelos, Marta; Hamann, Karen; Williams, Michael; Styles, David; Toma, Luiza; Shrestha, Shailesh; et al. (Frontiers in Sustainable Food Systems, 2021)
Well-managed legume-based food systems are uniquely positioned to curtail the existential challenge posed by climate change through the significant contribution that legumes can make toward limiting Green House Gas (GHG) emissions. This potential is enabled by the specific functional attributes offered only by legumes, which deliver multiple co-benefits through improved ecosystem functions, including reduced farmland biodiversity loss, and better human-health and -nutrition provisioning. These three critical societal challenges are referred to collectively here as the “climate-biodiversity-nutrition nexus.” Despite the unparalleled potential of the provisions offered by legumes, this diverse crop group remains characterized as underutilized throughout Europe, and in many regions world-wide. This commentary highlights that integrated, diverse, legume-based, regenerative agricultural practices should be allied with more-concerted action on ex-farm gate factors at appropriate bioregional scales. Also, that this can be achieved whilst optimizing production, safeguarding food-security, and minimizing additional land-use requirements. To help avoid forfeiting the benefits of legume cultivation for system function, a specific and practical methodological and decision-aid framework is offered. This is based upon the identification and management of sustainable-development indicators for legume-based value chains, to help manage the key facilitative capacities and dependencies. Solving the wicked problems of the climate-biodiversity-nutrition nexus demands complex solutions and multiple benefits and this legume-focus must be allied with more-concerted policy action, including improved facilitation of the catalytic provisions provided by collaborative capacity builders—to ensure that the knowledge networks are established, that there is unhindered information flow, and that new transformative value-chain capacities and business models are established.